The use of stainless steel to create contemporary artistic Arabic calligraphy sculptures / Zeneb Ali Abu Aish and Nor Azlin Hamidon - Ali Abu Aish, Zeneb; Hamidon, Nor Azlin (Faculty of Art & Design, 2022)
This paper examined the use of stainless steel in creating contemporary Arabic calligraphy sculptures. It discusses artworks' unique, innovative, and non-imitation stainless steel Arabic calligraphy. This study sheds light on this new field of modern Arabic calligraphy. The artworks of four famous artists were analysed in terms of how these works were created, the scripts or letters and alphabets used, and the type of calligraphy used. The type of contemporary art of Arabic calligraphy used includes verses from the Qur'an, poetry, famous sayings, and non-Arabic poems translated into Arabic letters. The interaction between sculptural Arabic calligraphy, stainless steel, and the environment or surrounding factors led to a contradictory three-way interaction, which increased the sculptural artistic act and creativity. The data were analysed using the descriptive analysis method and observation method. The samples analysed consist of fifteen sculptures. The finding revealed that these stainless steel carvings include intertwined Arabic scripts and letters. Arabic calligraphy employed varied between leafy Kufic, Moroccan Kufic, Diwani, Thuluth, Naskh, and even contemporary Arabic calligraphy. The sculptures' contents or phrases also varied between Quranic verses, poetry, novel, sayings, words, and sentences from the artist himself. As for the style, there is free Arabic calligraphy, new modern classic Arabic calligraphy, and modern classic Arabic calligraphy.